Proteomic analysis of protein lysine 2-hydroxyisobutyrylation (Khib) in soybean leaves - Wei Zhao; Ting-Hu Ren; Yan-Zheng Zhou; Sheng-Bo Liu; Xin-Yang Huang; Tang-Yuan Ning; Geng Li (BMC Plant Biology, 2023)
Abstract Background Protein lysine 2-hydroxyisobutyrylation (Khib) is a novel post-translational modification (PTM) discovered in cells or tissues of animals, microorganisms and plants in recent years. Proteome-wide identification of Khib-modified proteins has been performed in several plant species, suggesting that Khib-modified proteins are involved in a variety of biological processes and metabolic pathways. However, the protein Khib modification in soybean, a globally important legume crop that provides the rich source of plant protein and oil, remains unclear. Results In this study, the Khib-modified proteins in soybean leaves were identified for the first time using affinity enrichment and high-resolution mass spectrometry-based proteomic techniques, and a systematic bioinformatics analysis of these Khib-modified proteins was performed. Our results showed that a total of 4251 Khib sites in 1532 proteins were identified as overlapping in three replicates (the raw mass spectrometry data are available via ProteomeXchange with the identifier of PXD03650). These Khib-modified proteins are involved in a wide range of cellular processes, particularly enriched in biosynthesis, central carbon metabolism and photosynthesis, and are widely distributed in subcellular locations, mainly in chloroplasts, cytoplasm and nucleus. In addition, a total of 12 sequence motifs were extracted from all identified Khib peptides, and a basic amino acid residue (K), an acidic amino acid residue (E) and three aliphatic amino acid residues with small side chains (G/A/V) were found to be more preferred around the Khib site. Furthermore, 16 highly-connected clusters of Khib proteins were retrieved from the global PPI network, which suggest that Khib modifications tend to occur in proteins associated with specific functional clusters. Conclusions These findings suggest that Khib modification is an abundant and conserved PTM in soybean and that this modification may play an important role in regulating physiological processes in soybean leaves. The Khib proteomic data obtained in this study will help to further elucidate the regulatory mechanisms of Khib modification in soybean in the future.